Stages of Technologies and Technical Means Development for Fertilization and Plant Protection - Yu. S. Tsench; I. V. Sidorov (Сельскохозяйственные машины и технологии, 2024)
The experience of technological development of our country is an important source of ideas and approaches to the further development of agriculture based on domestic equipment and technologies. The study of its evolution necessitates the using of periodization. It is currently undeveloped for chemization of agriculture, more often being replaced by a set of key dates and biographies. So, it is nesessary to develop a holistic version of the structuring of chemization history. (Research purpose) To propose and substantiate the authors’ version of Russian agriculture chemization periodization. (Materials and methods) Monographs, legal acts, collected works and publications of outstanding scientists were studied using chronological, genetic and periodization methods of historical research (Results and discussion) The proposed periodization integrates previous historical ideas and hypotheses. The chemization of Russian agriculture has more than 250 years of history, which can be divided into 6 stages: preparatory (prehistory of chemization, which has three sub-stages), formative, extensive, stabilization, intensive and decentralized. The starting point is a publication of work «On lands fertilization» by A.T. Bolotov in 1770. Currently, the prerequisites for a new stage in the development of chemization are being formed, and it main attributes are digitalization, mechanization and biologization in the highest degree. (Conclusions) The proposed approach to structuring the history of Russian agriculture chemization is useful both for researchers and for training organization. The presence of clear guidelines increases the effectiveness of studying the historical aspects of agriculture, science and technology, which are so necessary for the professional and personal development of future agronomists and engineers.